2023
DOI: 10.3390/ma16020631
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Method for Predicting Corrosion Weight Gain of Uranium and Uranium Alloys

Abstract: As an irreplaceable structural and functional material in strategic equipment, uranium and uranium alloys are generally susceptible to corrosion reactions during service, and predicting corrosion behavior has important research significance. There have been substantial studies conducted on metal corrosion research. Accelerated experiments can shorten the test time, but there are still differences in real corrosion processes. Numerical simulation methods can avoid radioactive experiments, but it is difficult to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Figure 5 illustrates the ten-fold cross-validation curves for the three methods before and after the dataset undergoes SMOTE processing. Ten-fold cross-validation is widely used as it helps to reduce the uncertainty in the selection of the validation set [63,64]. It can be observed that, through the application of SMOTE, there is a significant improvement in the model performance, indicating that SMOTE effectively mitigates the issue of data imbalance.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…Figure 5 illustrates the ten-fold cross-validation curves for the three methods before and after the dataset undergoes SMOTE processing. Ten-fold cross-validation is widely used as it helps to reduce the uncertainty in the selection of the validation set [63,64]. It can be observed that, through the application of SMOTE, there is a significant improvement in the model performance, indicating that SMOTE effectively mitigates the issue of data imbalance.…”
Section: Data Preprocessingmentioning
confidence: 99%